Macroecenomic identification of the pricing factors on the Johannesburg Stock Exchange - G. D.I. Barr (South African Journal of Business Management, 1990)
This paper considers the main economic forces which drive the various sectors of the Johannesburg Stock Exchange, over the period 1979-1987. A factor-analysis approach identified these main forces as the price of gold, the short-term rate of interest, the performance of foreign stock markets, and local business confidence. The period considered is broken down into several subperiods in which these economic factors performed differently and where one or other dominated. This enables one to obtain a precise idea of which economic variables move which sectors and when.
Keywords: 650